2019
DOI: 10.2298/jsc180504070h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative response of Melissa officinalis L. and Valeriana officinalis L. leaves exposed to exogenous melatonin and excessive zinc and cadmium level

Abstract: Heavy metals disturb the redox homeostasis of the plant cell. The indolamine hormone, melatonin, protects plants from oxidative damage by directly scavenging reactive oxygen species or by stimulating the activity of antioxidant enzymes. The antioxidative role of melatonin in the leaves of two medicinal plants, lemon balm (Melissa officinalis L.) and valerian (Valeriana officinalis L.) that were treated with increased concentrations of Zn and Cd 24 h after sowing at an open field, were investigated. The plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The concentration is three times higher, which is expected since the leaves show greater antioxidant activity [29]. The authors have emphasized that melatonin might protect plants from stress conditions and to prevent injuries induced by oxidative stress at the cellular level, by elevating the activity of antioxidative enzymes in first growing phase of the plants [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration is three times higher, which is expected since the leaves show greater antioxidant activity [29]. The authors have emphasized that melatonin might protect plants from stress conditions and to prevent injuries induced by oxidative stress at the cellular level, by elevating the activity of antioxidative enzymes in first growing phase of the plants [19].…”
Section: Resultsmentioning
confidence: 99%
“…The identification and quantification of melatonin, as well as the analysis of the biochemical characteristics of lemon balm under the influence of heavy metals and exogenous melatonin, have not been conducted so far [19]. This paper examines the role of melatonin as a signaling molecule in signaling from the environment and mediating the response of plants exposed to the maximum allowable concentrations of cadmium and zinc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, greater SOD activity has been reported during chilling stress [42], waterlogging [44], alkaline stress [46], heavy metal stress [38], and drought stress [26]. Campos et al [25] reported that SOD activity was lower following the rehydration of Coffea arabica L. plants that had initially been exposed to drought stress, whereas Hodžić et al [40] described changes in SOD activity following the addition of melatonin under Cd and Zn stress in Melissa officinalis L. and Valeriana officinalis L. Interestingly, lower SOD activity was observed in Valeriana officinalis L. supplemented with both Zn and melatonin, whereas it increased when Zn was replaced with Cd. However, in the case of Melissa officinalis L., higher SOD activity was recorded after the addition of melatonin with Cd and Zn.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 95%
“…Stress Condition Exo-Melatonin Based Up-Regulated Antioxidants SOD, POD, GR, ASA, GSH CAT [37] Triticum aestivum cv. Heavy metals SOD, APX, GSH CAT, POD [38] Nicotiana tabacum L Heavy metals SOD, APX, CAT [39] Melissa officinalis L. Heavy metals SOD [40] Valeriana officinalis L. Heavy metals SOD [40] Cynodon dactylon L. Heavy metals SOD, POD, CAT, GR, APX [41] Solanum lycopersicum L. cv Acid rain stress SOD, POD, CAT, APX [42] Cucumis sativus L. Water stress SOD, POD, CAT [43] Malus baccata L. Waterlogging SOD. POD, CAT [44] Pisum sativum L. Oxidative stress SOD [45] Malus hupehensis Rehd.…”
Section: Crop Plantmentioning
confidence: 99%
“…However, to confirm this hypothesis in cannabis further investigation and additional studies are needed. Hodžić et al, (2019) observed changes in Ca and Mg concentrations of the pre-treated lemon balm (Melissa officinalis L.) plants w ith exogenous 0.1 mM melatonin and increased levels of zinc and cadmium. Their observations referring to MT impact on Cd and Zn uptake and translocation by lemon balm plants made them propose that melatonin can be used for phytoremediation purposes (Hodžić et al, 2019).…”
Section: Discussionmentioning
confidence: 90%